Performativity and Affect in Education - Ruitenberg, Claudia W. (Philosophical Inquiry in Education, 2015)
This essay examines the concept of performativity in relation to what are perceived to be reasonable and unreasonable affective responses to discourse. It considers how discourse, especially in classrooms and other educational contexts, produces effects, and how it is that those effects are sometimes seen as attached to the discourse, and sometimes as attached to the person who perceives and displays the effect. When discourse produces strong affective responses, sometimes the discourse itself is seen as unreasonable and in need of socializing (e.g., racist and homophobic slurs), and sometimes the person is perceived as “overreacting” to language that is not considered inherently affectively charged. Such distinctions, whether made explicitly or not, shape educational contexts and offer a hidden curriculum of “appropriate” affect. The essay traces the concept of performativity through the work of Austin, Derrida, Butler, and Cavell, and then extends it to affect theory to see how performativity can help us think through the provocation or production of feelings beyond individual psychological explanations.